(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Introduction: Sudden cardiac death is commonly an unexpected first cardiac event, often striking during the victim’s productive years. Cardiomyopathies are heterogeneous group of myocardium diseases with cardiac dysfunction, accounting for second largest sudden cardiac deaths after coronary artery disease. Aim of the study: This study aims to present the profile of deaths due to different cardiomyopathies with histopathological features of the heart. Materials and Methods: In this autopsy based cross sectional study, 138 sudden cardiac deaths including 24 cardiomyopathy cases were studied at Osmania General Hospital, Hyderabad, Telangana between October 2010- September 2012. Cases except decomposed and unknown with history of sudden cardiac death within a 24hrs span after initial event of cardiac illness and cardiomegaly as an incidental finding during autopsy were considered. Results: It revealed that among all sudden cardiac deaths (138 cases), 79% happened due to chronic ischemic heart disease and 17% due to cardiomyopathies of which hypertrophic cardiomyopathy accounted for 62.5%. Incidence of cardiomyopathy is predominant in males (79.2%). Most occurred in the 21-30 years’ age group. The mean heart weight is 548gms. The thickness of the left ventricle is in the range of 3-4cms in most cases (62.5%). In most cases (45.8%), the left ventricle is involved. Most death occurred in the initial 2 hrs after the onset of illness (62.5%). Conclusion: The study emphasizes that cardiomyopathies should be kept in mind to be a cause of sudden death in perfectly normal individual.